RANCANG BANGUN PERANGKAT LUNAK KONVERSI KATA BAHASA JEPANG BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract It is known that the Japanese is a nation that has advanced knowledge of technology so that if you are mastered their language then you'll find it easier to study  about their science and technology.Considering the importance of studying the Japanese language,schools equal the junior and senior high school in Indonesia is now starting to include the Japanese language lessons as one of the subjects taught. To help achieve that,it has been made ​​a Japanese learning application that utilizes web technology. The objectives to be achieved is to build a web converting Japanese word that can easily be opened in the phone which is expected to be useful for students of junior high, high school or community. The results in this study is a website design software conversion web-based Japanese word that can be used as learning materials to introduce the Japanese word and help to practice in writing Japanese characters properly. Keyword  Japanese language words, Convertion, Web